Management and operational practices of water and sewerage companies in Italy and Argentina - Ponce Díaz, Santiago Juan (2018)
Fil: Ponce Díaz, Santiago Juan. Universidad Nacional del Litoral. Facultad de Ciencias Económicas; Argentina.